KEWAJIBAN DIDAMPINGI PENASIHAT HUKUM TERHADAP TERSANGKA/TERDAKWA YANG TIDAK MAMPU YANG DIANCAM HUKUMAN 5 TAHUN PENJARA ATAU LEBIH SESUAI KETENTUAN PASAL 56 (1) KUHAP - Dr Andi Akram; Juliani Juliani SH (VERITAS, 2018)
With the number of suspects receiving less humane treatment from investigators atthe investigation level, the application of the provisions of article 56 paragraph (1)of the Criminal Procedure Code, especially at the Police level as Investigator,there are still many who have not been able to realize it. Whereas the applicationof Article 56 Paragraph (1) of the Criminal Procedure Code regarding the rightsof suspects to obtain legal aid at the trial level has been partially implemented,especially in the District Courts located in major cities, although there are stillsome courts that have not implemented the provisions Article 56 paragraph (1) forthe defendant who can not afford it. Whereas the implementation of the legalassistance process for suspects/accusers as mandated in article 56 (1) of theCriminal Procedure Code is not always smooth as expected by all parties, with theargument that there is no legal counsel to be appointed in the jurisdiction, thedeliberate misconception that the appointment of a legal counselor necessarilyrequires a special budget, and in such an institution is not budgeted, it is clearly aconstraint factor in enforcing the concept of article 56 (1) of the CriminalProcedure Code. Seeing several laws and regulations governing the concept oflegal assistance to the suspect, that all existing laws are currently meeting theexpected criteria, as mandated in article 56 paragraph (1) of the CriminalProcedure Code, but still exist some implementing regulations as a complementthat have not been made.